تأثير العمر على بعض الصفات الجسمية لإناث حملان الضأن البربري الليبي من الفطام وحتى التسويق في منطقة بلقس بالجبل الأخضر – ليبيا (Albayan Scientific Journal, 2023)
This study was conducted to find out the effect of age on body weight and some external physical characteristics and the correlation coefficient of live body weight with these characteristics on 9 female of libyan Barbary lambs from the age of weaning (three months) until the age of marketing in the Belges region of Jabal Al-Akhdar - Libya. The study was conducted from March to May 2019 and measurements were taken every two weeks and lasted for two months. The results were as follows: Body weight recorded a significant P
Keywords: Libyan Barbary female sheep; correlation rate; body weight